Mendeley Training: Scientific Writing Support for Prospective Teachers in Aceh Utara - Ucia Mahya Dewi; Wulanda; Arlin Maya Sari; Al-Furqan; Islami Fatwa (PT FORMOSA CENDEKIA GLOBAL, 2023)
This Community Service activity aims to explain the use and benefits of the Mendeley application to prospective teachers. This activity was carried out for two days from 5-6 June 2023. The stages of this activity consisted of the preparation stage, the implementation stage and the evaluation stage. The community service activities that have been carried out have succeeded in increasing the knowledge and understanding of participants in using and utilizing the Mendeley application for writing scientific papers.